Hand injuries in boxing - Loosemore, M.; Beardsley, C.; Lallemand, B. (ASPETAR Sports Medicine Journal, 2016)
Boxing has historically been primarily associated with head injuries, particularly concussion. More recently, it has become clear that hand injuries may be as common, if not even more common. Indeed, injury surveillance reporting by the British Amateur Boxing Association suggests that the incidence of hand injury does exceed that of head injury1. An understanding of the common types of hand injury in boxing is therefore important for the sports medicine physician working with boxers and athletes in other similar contact sports.